2013
DOI: 10.1590/s1806-66902013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento na barra de tração de um trator agrícola com diferentes relações de peso e potência

Abstract: RESUMO-O ensaio do trator em solo agrícola é uma das maneiras de se obter informações, principalmente no que diz respeito ao seu desenvolvimento de tração. O rendimento na barra de tração é frequentemente usado para comparar ou avaliar tratores. Entretanto, o rendimento na barra de tração é afetado pelas condições da superfície de deslocamento, pela relação de engrenagens e pela relação entre o peso e a potência do trator. O objetivo do presente trabalho foi avaliar o rendimento na barra de tração de um trator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
1
10
0
5
Order By: Relevance
“…In compatible conditions with this study MONTEIRO et al (2013) evaluated the efficiency of the 4x2 FWD tractor equipped with diagonal tires with a displacement speed of 1.94 m s -1 , where it was found that in the power range in the drawbar of 15 to 20 kN , efficiency values of 50.9 and 54.1%, respectively. These values are lower than those presented in this study.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In compatible conditions with this study MONTEIRO et al (2013) evaluated the efficiency of the 4x2 FWD tractor equipped with diagonal tires with a displacement speed of 1.94 m s -1 , where it was found that in the power range in the drawbar of 15 to 20 kN , efficiency values of 50.9 and 54.1%, respectively. These values are lower than those presented in this study.…”
Section: Resultsmentioning
confidence: 97%
“…The tire allows the torque of a tractor to be transmitted to the ground and enables it to draw a certain load in addition to moving. Tire traction depends on a number of factors including tire geometry (width, diameter, and section height), tire type (diagonal or radial), claw type, internal pressure, dynamic load on the axle and soil type and conditions (MONTEIRO et al 2011;MONTEIRO et al 2013;GABRIEL FILHO et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rinaldi et al (2016) relação a favor da força de tração. A adição do lastro em determinadas condições de trabalho, permite maior aderência e rendimento operacional do trator, MONTEIRO et al (2013), também obtiveram conclusões semelhantes.…”
Section: Resultsunclassified
“…Existem basicamente duas maneiras de se ensaiar tratores pela barra: utilizando como freio um segundo trator engatado à barra de tração, que proporciona força contrária ao trator ensaiado, como em GOMES et al (2016); ou pelo emprego de um carro dinamométrico engatado à barra de tração, como em MONTANHA et al (2011), MONTEIRO et al (2013) e FIORESE et al (2015.…”
Section: Introductionunclassified